Educational Problems in Indonesia in the Excitement of Building the Golden Generation 2045 - Ferdianto, Muhammad (Journal of Social Science and Education Research, 2024)
The preamble to the Constitution of the Republic of Indonesia in 1945 is a reference for great ideals so that this nation's ideology is created. In Indonesia itself, the fourth paragraph of the preamble to the Constitution of the Republic of Indonesia in 1945 has the goal of "Educating the life of the nation". However, more than half a century after the independence of the Republic of Indonesia, all people still do not have access to formal education as it should and lack of awareness that non-formal and informal education can also reduce the people from the failure of the golden generation later. Based on statistical data issued by the Central Statistics Agency, at the provincial and district levels, it shows that there are certain groups of children who mostly come from poor families so that they are unable to continue their education to the next level. If we look at the development of formal education until now, many of our friends have dropped out of school due to lack of economic costs. The problem of building a generation with character is a problem for Indonesian education, starting from the gap in infrastructure between regions such as transportation and bookstores. So to galvanize the successors that the nation and state hope to have in the future, formal informal and non-formal education as the basis for young people has the characteristics of people who are not only educated but humane. Therefore, we wrote this article with the aim of analyzing the problems of education in Indonesia as well as solutions to the current state of the nation which is an obstacle to a golden Indonesia, the challenge of the Indonesian generation in stimulating the expected and aspired successor.